Arsenic exposure and mortality: a case-referent study from a Swedish copper smelter. Issue 1 (February 1978) - Axelson, O; Dahlgren, E; Jansson, C D; Rehnlund, S O
Abstract : An increased mortality from lung cancer, cardiovascular disease, haematolymphatic malignancy and cirrhosis of the liver has been reported among smelter workers and others exposed to arsenic. This study uses the case-referent (case-control) technique and is concerned with workers in a copper smelter in a complex work environment, characterised by the presence of trivalent arsenic in combination with sulphur dioxide and copper, and also with other agents. Lung cancer mortality was found to be increased about five-fold and cardiovascular disease about two-fold, showing a dose-response relationship to arsenic exposure. Mortality from malignant blood disease (leukaemia and myeloma) and cirrhosis of the liver was also slightly increased. This mortality pattern among the smelter workers is consistent with earlier reports. An increased mortality from cardiovascular disease in this type of industry is of particular interest as it has been reported only once before.